(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2024)
Researchers from all around the world are interested in nanoparticles of zinc oxide (ZnO-NPs) because of their extensive biological functions. In addition to be less toxic and biodegradable, they can dramatically increase pharmacophore biological activity. ZnO-NPs are the most commonly utilized metallic nanoparticle in electronics and optics due to their distinct visual and chemical characteristics, which may be easily altered by modifying the structure and broad bandgap. Repetition their affordability, biocompatibility, and biodegradability, ZnO-NPs are a viable option as a nanocarrier for conventional medications. ZnO NPs’ tiny particle size and large surface area can improve surface reactivity by enhancing antibacterial activity. Additionally, as the surface characteristics of nanomaterials modify their interactions with cells, this may prevent ZnO NPs from having their intended antimicrobial effect. Surface modifications covering ZnO NPs can therefore play a role in moderating antimicrobial activity. ZnO NPs’ antibacterial activity may be increased by adding surface modifiers containing groups harmful to microorganisms. This article discusses in detail the biopotency of ZnO-NPs in antibacterial, anti-inflammatory, antifungal, antidiabetic, anticancer, antioxidant, and antiviral applications. Conclusion : It has been demonstrated that ZnO-NPs perform a wide variety of biological functions.